2021
DOI: 10.3389/fncel.2021.684762
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Neurotropic Viruses in Fast Axonal Transport: Mechanisms, Potential Role of Host Kinases and Implications for Neuronal Dysfunction

Abstract: Much remains unknown about mechanisms sustaining the various stages in the life cycle of neurotropic viruses. An understanding of those mechanisms operating before their replication and propagation could advance the development of effective anti-viral strategies. Here, we review our current knowledge of strategies used by neurotropic viruses to undergo bidirectional movement along axons. We discuss how the invasion strategies used by specific viruses might influence their mode of interaction with selected comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 177 publications
(251 reference statements)
0
13
0
Order By: Relevance
“… 23 In addition, genetically manipulated viruses have been used to map neural pathways because they are capable of anterograde and retrograde trans-synaptic migration. 22 , 24 Other authors have suggested that coronaviruses, 25 including the SARS-CoV-2 virus. 26 , 27 enter the CNS via the nasal cavity and olfactory system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 In addition, genetically manipulated viruses have been used to map neural pathways because they are capable of anterograde and retrograde trans-synaptic migration. 22 , 24 Other authors have suggested that coronaviruses, 25 including the SARS-CoV-2 virus. 26 , 27 enter the CNS via the nasal cavity and olfactory system.…”
Section: Discussionmentioning
confidence: 99%
“… 14 The SARS-CoV-2 virus could bind to papillae in the tongue; enter the neurons (since there is no blood brain barrier in the periphery, rather it is called blood-nerve interface 40 ); and move along the axon, highjacking the transport routes used physiologically by the neuron to carry particles as other viruses do. 24 , 26 , 41 Alternatively, a “trojan horse” mechanism 42 could be involved: the virus could “hitch a ride” in cells like lymphocytes or macrophages and travel along the axons to the CNS. Given the presence of T cells and macrophages in the human trigeminal nerve and ganglion this seems feasible.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the intriguing possibility that it represents a neuroprotective mechanism designed to limit viral spread, as proposed previously (Mukherjee et al, 2013 ; Sundaramoorthy et al, 2020 ). Neuronal processes, especially axons, are highly reliant on microtubule-dependent transport for function and survival (De Vos et al, 2008 ; Magiera et al, 2018 ; Guedes-Dias and Holzbaur, 2019 ; Kelliher et al, 2019 ; Koppers and Farías, 2021 ), and several neurotropic viruses including Theiler's virus, herpes simplex virus, poliovirus, rabies virus, and West Nile virus (WNV), transit in axons, likely relying on microtubule-dependent transport to reach their targets (Salinas et al, 2009 and reviewed in Richards et al, 2021 ). Thus, the significant increase in infection and death of neuronal somas in SARM1-depleted cultures (with delayed degeneration of neuronal processes) suggests that ZIKV can be transported in this way too and that SARM1-dependent degeneration of neuronal processes limits its spread to neuronal somas.…”
Section: Discussionmentioning
confidence: 99%
“…The SARM1 TIR domain has NAD + consuming glycohydrolase (NADase) activity, considered critical for its prodegenerative capacity (Essuman et al, 2017 ; Horsefield et al, 2019 ), although it has additional NADP hydrolase and base exchange activities that could also play important roles (Angeletti et al, 2021 ). As axons are often used by neurotropic viruses to enter neuronal and glial somas where the cellular machinery they use to replicate is located (Richards et al, 2021 ) it has been suggested that the known response of SARM1 to bunyavirus or rabies virus infection (both negative strand RNA viruses) could represent a mechanism to limit the spread of neurotropic virus (Mukherjee et al, 2013 ; Sundaramoorthy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other neurotropic molecules are of extrinsic origins, including bacterial or fungal toxins (such as cholera toxin, tetanus toxin, and botulinum neurotoxin) and lectins (such as wheat germ agglutinin (WGA) and phaseolus vulgaris leucoagglutinin (PhA-L)) [35,[55][56][57][58]. A number of viruses, including the herpes simplex viruses, poliovirus, rabies virus, and bovine herpesvirus 5 (BHV5), are also neurotropic [34,36,[59][60][61]. A majority of these neurotropic molecules/viruses have designated binding receptors identified on neuronal cells, and thus could enter neurons through receptor-mediated endocytosis.…”
Section: Neurotropism and Neuropathology Of Sars-cov-2?mentioning
confidence: 99%